Penerapan pupuk hayati dalam meningkatkan produksi jagung (Zea mays L.) di Kabupaten Limapuluh Kota - Yun Sondang; Ramond Siregar; Khazy Anty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The objectives of this activity are to disseminate the results of research to increase corn production in Limapuluh Kota District, to increase knowledge and skills of the community in making and using biofertilizers, and corn cultivation techniques. The method used is